Discovery and Characterization of a Cellular Potent Positive Allosteric Modulator of the Polycomb Repressive Complex 1 Chromodomain, CBX7. Issue 10 (17th October 2019) - Lamb, Kelsey N.; Bsteh, Daniel; Dishman, Sarah N.; Moussa, Hagar F.; Fan, Huitao; Stuckey, Jacob I.; Norris, Jacqueline L.; Cholensky, Stephanie H.; Li, Dongxu; Wang, Jingkui; Sagum, Cari; Stanton, Benjamin Z.; et al.
Summary: Polycomb-directed repression of gene expression is frequently misregulated in human diseases. A quantitative and target-specific cellular assay was utilized to discover the first potent positive allosteric modulator (PAM) peptidomimetic, UNC4976, of nucleic acid binding by CBX7, a chromodomain methyl-lysine reader of Polycomb repressive complex 1. The PAM activity of UNC4976 resulted in enhanced efficacy across three orthogonal cellular assays by simultaneously antagonizing H3K27me3-specific recruitment of CBX7 to target genes while increasing non-specific binding to DNA and RNA. PAM activity thereby reequilibrates PRC1 away from H3K27me3 target regions. Together, our discovery and characterization of UNC4976 not only revealed the most cellularly potent PRC1-specific chemical probe to date, but also uncovers a potential mechanism of Polycomb regulation with implications for non-histone lysine methylated interaction partners. Graphical Abstract: Highlights: CBX7 mESC reporter line revealed UNC4976 as a more potent antagonist than UNC3866 Unique mechanism of action for UNC4976 as a modulator of DNA/RNA binding to CBX7 UNC4976 reduces CBX7/PRC1 CHIP peaks on chromatin with greater efficacy than UNC3866 UNC4976 reactivates PRC1 target genes more effectively than UNC3866 in HEK293 cells Abstract : Lamb et al. describe the discovery of UNC4976 as a cellularly efficacious inhibitor of CBX7. Despite similar potency, selectivity, and permeability to previously published probe UNC3866, UNC4976 possesses a unique mechanism of action as a positive allosteric modulator of nucleic acid binding to CBX7 that rationalizes its enhanced cellular activity.